Behavioral Intention to Use IoT Health Device: The Role of Perceived Usefulness, Facilitated Appropriation, Big Five Personality Traits, and Cultural Value Orientations - Tommy Prayoga; Juneman Abraham (Institute of Advanced Engineering and Science, 2016)
As one of the biggest technology breakthrough, Internet of Things (IoT) has been gaining much attention in every industry it’s involved in. Especially in the healthcare sector, IoT health devices have been proved to have a great impact on individual’s health regulation. Through many beneficial features from tracking sleep patterns to tracking chemicals in the blood, individuals will gain a better understanding of their body and how to keep it healthy. However, great benefit is one thing, and it does not immediately equal users’ acceptance. In this study, we seek to find elements that we propose to have an impact in predicting user’s intention of using IoT health device and integrate them into a model. We will analyze user’s technology acceptance from the perspective of Technology Acceptance Model, using Perceived Usefulness as the main predictor for Behavioral Intention. We also integrate Personality Traits and Facilitated Appropriation as factors to determine Perceived Usefulness, and finally using Hofstede’s Cultural Value, we seek to determine the antecedent of Facilitated Appropriation. The research design was correlational predictive, with path analysis technique. Participants of this study were 186 college students from IT campus (75 males, 111 females; mean of age = 20.86 years of old, standard deviation of age = 2.01 years) across Greater Jakarta. The results showed that Perceived Usefulness can predict intention to use the device. However, Personality Traits were found to be irrelevant in predicting perceived usefulness. Only Facilitated Appropriation could predict perceived usefulness. Among cultural values proposed, only the Long-term Orientation can predict user’s tendency to engage in Facilitated Appropriation. Also, we did not find any correlation between age and all technology acceptance factors (Behavioral Intention, Perceived Usefulness, and Facilitated Appropriation).